2015
DOI: 10.3329/jninb.v1i1.22944
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable and Non-Modifiable Risk Factors of Stroke: A Review Update

Abstract: Stroke is the third most common cause of death in industrialized countries. Stroke is the most important cause of morbidity and longterm disability in Europe as well as in other industrialized nations. Prevalence rate was higher among men compared with women 3.44 and 2.41 per 1000 respectively. Data from the Northern Manhattan study showed the age adjusted incidence of first ischemic stroke per 100,000 was 88 in Whites 191 in Blacks and 149 in Hispanics. Black has almost thrice the risk of first ever stroke co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 24 publications
6
23
0
Order By: Relevance
“…This was in concurrence with the findings of Sridhar Srimath Tirumala, Ranjan Amit (70% males and 30% females). 7,8 Out of141 patients it was found that 41 patients were< 45 years and 99 were >45 years From our study we observed that in the younger age group of < 45 years, the age between 31-45(63.4%) was at a higher risk which was comparable with the study conducted by Deepadharshan Huliyapa et al 9 . From our study it was found that the common risk factors among young were Alcohol consumption (78%), Hypertension (60.9%), Smoking (63%), in contrast to the study conducted by Masaraf Hussian, Shri Ram et al (2018).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This was in concurrence with the findings of Sridhar Srimath Tirumala, Ranjan Amit (70% males and 30% females). 7,8 Out of141 patients it was found that 41 patients were< 45 years and 99 were >45 years From our study we observed that in the younger age group of < 45 years, the age between 31-45(63.4%) was at a higher risk which was comparable with the study conducted by Deepadharshan Huliyapa et al 9 . From our study it was found that the common risk factors among young were Alcohol consumption (78%), Hypertension (60.9%), Smoking (63%), in contrast to the study conducted by Masaraf Hussian, Shri Ram et al (2018).…”
Section: Discussionsupporting
confidence: 87%
“…patients. [12][13][14] From our study, the modifiable risk factors which were recorded are hypertension, cardio vascular disorder, Diabetes Mellitus, Dyslipidaemia and Life style related were Smoking, Alcohol consumption, Obesity which was comparable to the study conducted by MS Jahirul hoque choudhary et al (2015) [15][16][17][18] . From our study, one male Pediatric case was recorded.…”
Section: Discussionsupporting
confidence: 86%
“…Risk factors of stroke can be classified as modifiable and non-modifiable [6]. Non-modifiable risk factors are unpreventable such as age, race and heredity whilst modifiable factors are controllable such as hypertension, cholesterol, diabetes and obesity [7]. This study identified and quantified the effect of stroke modifiable risk factors in SA using classical and Bayesian logistic regression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis was conducted in China to investigate modifiable and non-modifiable risk factors of ischemic stroke and found that cholesterol and diabetes were significantly associated with ischemic stroke [6]. Logistic regression was used to identify the modifiable and non-modifiable risk factors of stroke and the study findings showed that hypertension and diabetes were prevalent in old aged white males [7]. Cox proportional hazards model was used to investigate modifiable risk factors associated with stroke incidence in very old people in Sweden.…”
mentioning
confidence: 99%
“…8 A stroke is occasionally treated with thrombolysis, but usually with supportive care like speech therapy, physiotherapy and occupational therapy and secondary prevention with antiplatelet drugs, blood pressure control, statins, and in selected patients with carotid endarterectomy and anticoagulation. [9][10] Epidemiologic studies of the risk factors for stroke [10][11][12] For the detection of stroke, CT scan is considered the first line investigation due to its availability and exquisite sensitivity for detection of blood and infarction.…”
mentioning
confidence: 99%